Towards operationalization of NextGen seasonal forecasting systems in West Africa: Stocktaking of the regional capacity building initiative - Segnon, Alcade C; Obossou, Esdras; Ali, Abdou; Houngnibo, Mandela C.; Minoungou, Bernard; Mohamed, Hamatan; Zougmoré, Robert B. (Accelerating Impacts of CGIAR Climate Research for Africa, 2023)
In 2022, AICCRA through its regional partner AGRHYMET has capacitated West African National Meteorological and Hydrological Services (NMHS) on NextGen seasonal climate forecasting systems. Based on a case study of NMHSs of 11 countries, this Info Note takes stock of the outcomes and lessons learnt from the regional capacity development initiative. It also provides some reflections on the operationalization of NextGen seasonal forecasting systems in the region. More than 70% of the respondents found the trainings useful or very useful in improving their work on seasonal forecasting. Following their participation to the training events, about 39% of respondents have improved or updated seasonal forecasts using the PyCPT, while about 28% carried out follow-up activities and disseminated PyCPT knowledge to their colleagues and staff. Main challenges to operationalizing the NextGen approach and using the PyCPT tool include the lack of consideration of hydrologic parameters, the difficulty of setting up the PyCPT tool, the lack of basic programming skills, and the issue of data availability. The operationalization of NextGen forecasting systems will require continuous capacity building and improving the tools by integrating other climatic parameters relevant for agriculture and food systems as well as adapting to hydrological forecasting and integrating a diversity of data sources. Lessons learnt from this stocktaking will support the AICCRA Additional Financing activities and other regional initiatives such as the Food Systems Resilience Program for effective capacity development of NMHS to enable effective climate information services for the prevention and management of agricultural and food crises in West Africa and the Sahel.